2007
DOI: 10.1248/bpb.30.1358
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic Effects of Fluorotelomer Alcohols for Human Estrogen Receptor Isoforms .ALPHA. and .BETA. in Vitro

Abstract: The present study demonstrates the estrogenic effects of fluorotelomer alcohols (FTOHs). In a yeast two-hybrid assay, treatment with 1H,1H,2H,2H-perfluorooctan-1-ol (6:2 FTOH), 1H,1H,2H,2H-perfluoro-decan-1-ol (8:2 FTOH) and 2,2,3,3,4,-4,5,5,6,6,7,7,8,8,9,9,10,10,10-nonadecafluoro-1-decanol (NFDH) showed a dose-dependent interaction between the human estrogen receptor (hER) isoforms hERa a or hERb b ligand-binding domain and coactivator TIF2, whereas there were no estrogenic effects of perfluorooctane sulfonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 10 publications
3
24
0
Order By: Relevance
“…36) The assay has also been used to determine the estrogenic activity of test chemicals. 37) Novel E2 analogs, including orthoester 2k, were synthesized by Kato,34) and we investigated the affinity of each chemical for hERα and hERβ. Finally, we selected orthoester 2k as a novel ERα-specific agonistic ligand, as orthoester 2k was found to dosedependently induce chemiluminescence on hERα yeast two-hybrid assay [ Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36) The assay has also been used to determine the estrogenic activity of test chemicals. 37) Novel E2 analogs, including orthoester 2k, were synthesized by Kato,34) and we investigated the affinity of each chemical for hERα and hERβ. Finally, we selected orthoester 2k as a novel ERα-specific agonistic ligand, as orthoester 2k was found to dosedependently induce chemiluminescence on hERα yeast two-hybrid assay [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…36) The exposure concentrations of orthoester 2k (concentration ranges tested: 0.36, 0.73, 1.5, 2.9, 5.8, 11.7 and 23.3 µM), and E2 (31-2000 pM) were selected based on the results of a previous study. 37) All experiments were performed in triplicate for each compound. Animals --Medaka (d-rR strain) have been kept in glass tanks for several years in our laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…These concentrations are still substantially higher than the concentrations found among the general population (average PFOA concentration in the US population is 4-5 ng/ml) (11). Moreover, PFOA or PFOS may have estrogenic effects, although the evidence from in vivo or in vitro studies is inconsistent (12)(13)(14)(15)(16)(17), and their potential effects on hormones, including prolactin, oxytocin, and estrogen may influence lactation. It is thus important to study if these compounds affect lactation at the concentrations found in humans.…”
Section: Perfluorinated Chemicals and Breastfeeding Durationmentioning
confidence: 94%
“…In vitro studies using human cells have reported following endocrine effects for fluorotelomer alchohols: 8:2 FTOH and 6:2 FTOH had potential estrogenic effects by inducing the proliferation of MCF-7 breast cancer cells in E-screen assay; by up-regulating of the estrogen receptor ; by interacting with the human estrogen receptor alpha and beta in vitro (Ishibashi H et al, 2007). Moreover, 8:2 FTOH showed the capacity to decrease testosterone levels in the human adrenal corticocarcinoma cell line (Liu et al, 2010b) but did not interfere with androgen receptor activation (Rosenmai et al, 2012).…”
Section: Human Health Effects Of Ftohmentioning
confidence: 99%
“…Fluorotelomer alcohols have been shown to exert estrogenic activity in MCF-7 cells, in a yeast two-hybrid assay and in aquatic organisms where 6:2 FTOH has been characterised as a stronger xenoestrogen than 8:2 FTOH (Ishibashi et al, 2008;Maras et al, 2006;Vanparys et al, 2006;Wang et al, 2012). According to Ishibashi et al (2007) treatment with 6:2 FTOH, 8:2 FTOH and NFDH (nonadecafluoro-1-decanol) show a dose-dependent interaction with the human estrogen receptor (hER), and rank the estrogenic effects for hERα and hERβ in the descending order of 17β-estradiol>>> 6:2 FTOH > NFDH > 8:2 FTOH. Waterborne exposure of both 6:2 and 8:2 FTOH alter the plasma levels of testosterone and estradiol and 8:2 FTOH adversely impair reproductive success in the offspring of zebrafish (Liu et al, 2010a;Liu et al, 2009).…”
Section: Ftohsmentioning
confidence: 99%